Security-constrained optimal generation scheduling in large-scale power systems - Martinez-Crespo, J.; Usaola, J.; Fernandez, J.L. (IEEE transactions on power systems, 2006)
This paper presents an approach to determine the optimal daily generation scheduling based on the Spanish electricity market rules. The Spanish power system considers the pool-based daily market and the technical constraints resolution as two different and consecutive processes. After the daily market has been cleared, a centralized constraints resolution process is applied to this initial scheduling through the redispatch of previously matched energy. In this paper, an algorithm based on Benders decomposition, arranged in three levels, is proposed to solve the technical constraints solution process in order to define a preventive secure dispatch. The constraints resolution process includes a full ac network and security model. This method determines the active power committed to each generating unit so as to minimize the energy redispatch cost subject to dispatch, network, and security constraints. The solution also provides the reactive power output of the generating units, the value of the transformers taps, and the committed voltage control devices. The model has been tested in an actual example of the Spanish power system. Some relevant results are reported.